Degradability of polylactide and its blend with poly[(R, S)-3-hydroxybutyrate] in industrial composting and compost extract. (July 2015) - Sikorska, Wanda; Musiol, Marta; Nowak, Bozena; Pajak, Jolanta; Labuzek, Sylwia; Kowalczuk, Marek; Adamus, Grazyna
Abstract: Degradation process of the rigid films prepared from polylactide (PLA) and its blend with poly[(R, S)-3-hydroxybutyrate] (PLA/a-PHB) in an industrial composting pile and in extracts from industrial compost was conducted. The significant changes in the number average molar mass (Mn ) of the PLA and PLA/a-PHB samples without mass loss up to the 21 days of the experiment indicated that abiotic hydrolysis is the main process that occurs during the first weeks of the incubation of these samples in each environments studied. The observed progressive decrease in pH of sterile extract (SE) at invariable pH of the nonsterile extract (NSE) indicates that microbes present in compost can assimilate the products of abiotic hydrolysis of the incubated samples. The influence of microorganisms present in the compost on the (bio)degradation process of PLA and PLA/a-PHB was proved through 1 H NMR and ESI-MS analysis of the compost extracts collected after specific degradation time periods. Highlights: The industrial composting process of PLA rigid films was performed. In the composting process the hydrolysis of PLA is accompanied by microorganisms actions. Microorganisms present in compost are capable to assimilation of water soluble PLA oligomers.